MnTaO2N: Polar LiNbO3‐type Oxynitride with a Helical Spin Order1. (21st November 2014) - Tassel, Cédric; Kuno, Yoshinori; Goto, Yoshihiro; Yamamoto, Takafumi; Brown, Craig M.; Hester, James; Fujita, Koji; Higashi, Masanobu; Abe, Ryu; Tanaka, Katsuhisa; Kobayashi, Yoji; Kageyama, Hiroshi
Abstract The synthesis, structure, and magnetic properties of a polar and magnetic oxynitride MnTaO2N are reported. High‐pressure synthesis at 6 GPa and 1400 °C allows for the stabilization of a high‐density structure containing middle‐to‐late transition metals. Synchrotron X‐ray and neutron diffraction studies revealed that MnTaO2N adopts the LiNbO3‐type structure, with a random distribution of O2− and N3− anions. MnTaO2N with an "orbital‐inactive" Mn2+ ion (d5; S=5/2) exhibits a nontrivial helical spin order at 25 K with a propagation vector of [0, 0, δ] (δ≈0.3), which is different from the conventional G‐type order observed in other orbital‐inactive perovskite oxides and LiNbO3‐type oxides. This result suggests the presence of strong frustration because of the heavily tilted MnO4N2 octahedral network combined with the mixed O2−/N3− species that results in a distribution of (super)‐superexchange interactions.